STUDY OF PRODUCTION PROCESS OF IRON METAL WITH HIGH TEMPERATURE ELECTROLYSIS AND REDUCTION PROCESS WITH HYDROGEN: LITERATURE REVIEW - Alfaraby, Farchan
Steel is the most commonly used alloy in the world with a demand of about 2 billion tons/year. Blast Furnace as a dominant reactor in steel production generates 2.15 ton CO2 gas/ton pig iron. CO2 gas, in outside of carbon cycle like blast furnace’s emission, can not be well absorbed by plant. Unabsorbed CO2 gas would be collect in atmosphere so that it can initiate greenhouse effect. Greenhouse effect causes global warming. Starting from global warming issues, several alternative processes emerged, namely high-temperature electrolysis and reduction with hydrogen. The high-temperature electrolysis process produces oxygen as by product, and reduction with hydrogen produces water vapor as by-product. In evaluating the potential use of alternative processes in the future, a feasibility analysis is needed both in technical and economic aspects. The literature study began by collecting journals, books, and sources of information related to the characteristics of iron ore, high-temperature electrolysis processes, reduction processes with hydrogen, the use of an inert anode in the electrolysis of iron ore, the performance of the electrolyte used, the production of hydrogen, the difference of CO and H2 gas as reductor. The literature that has been collected is then studied and analyzed to obtain information which is then used to make a comprehensive discussion to answer the objectives that have been formulated. The results of this literature study indicate that research on high-temperature electrolysis and reduction with hydrogen has not been widely carried out. In addition, several important points were obtained including: (1) Demand of production of hydrogen from electrolysis of water is very dependent on future policies such as the price of electricity because its production price is expensive, namely USD 10.3/kg H2 gas; (2) The use of the H2 gas reductor requires a higher energy supply and more compact reactor compared to that of syngas; (3) molten MgO-CaO-Al2O3-SiO2 has the potential to be used in iron production as an electrolyte because it can be operated at high temperature; (4) Iridium has the potential to be used as an inert anode for the electrolysis of iron ore, but its quantity is very limited; (6) Based on the feasibility analysis, Molten Oxide Electrolysis (MOE) technology has the potential to be used in the future because of low CAPEX, low CO2 gas emissions, and high iron metal production rate. The problem of finding abundant inert anodes for MOE technology is very crucial to realize an environmentally friendly process so that the research is interesting to study further.